2022
DOI: 10.2147/clep.s338149
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Bispebjerg Acute Cohort: Database Formation, Acute Contact Characteristics of a Metropolitan Hospital, and Comparisons to Urban and Rural Hospitals in Denmark

Abstract: Purpose To present a metropolitan cohort, Bispebjerg acute cohort (BAC), and compare patient characteristics and outcomes with patients from urban and rural hospitals in Denmark. Patients and Methods We linked data from seven Danish nationwide registries and included all acute contacts to non-psychiatric hospitals in the years 2016–2018. Acute hospital contacts to Bispebjerg and Frederiksberg Hospital constituted BAC, representing a solely metropolitan/urban catchment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…A recent study investigated all acute somatic hospital contacts in Denmark in the period 2016–2018. Amongst others, the study found 25.4–28.1% of hospitalizations had an non-specific diagnosis, either R “symptoms and signs” or Z “other factors” [ 26 ]. In the current study, among patients calling the emergency number with chest pain, the combined non-specific R and Z diagnoses, accounted for nearly half (47%) of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study investigated all acute somatic hospital contacts in Denmark in the period 2016–2018. Amongst others, the study found 25.4–28.1% of hospitalizations had an non-specific diagnosis, either R “symptoms and signs” or Z “other factors” [ 26 ]. In the current study, among patients calling the emergency number with chest pain, the combined non-specific R and Z diagnoses, accounted for nearly half (47%) of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…To consider the entire length of the patients’ hospital stay, we combined sequential Danish National Patient Registry (DNPR) contacts within ≤4 hours, considering contacts with both somatic and psychiatric departments and all types of inpatient/outpatient and acute/elective contacts. 4 We only included contacts with at least one acute and one inpatient contact. Thereby, patients with a contact with the ED without outright hospitalization were not included.…”
Section: Methodsmentioning
confidence: 99%
“…Since four-digit ICD-10 grouping has been shown to be an inadequate way of categorizing diseases, we conducted our own clinically meaningful grouping of discharge diagnoses for our population ( Supplementary Materials; Table S1 ). 4 , 21 , 22 We selected 14 laboratory blood tests to represent a standard ED package, and reference values were drawn directly from the respective laboratories. Initial screening of the frequency of these tests was done: tests missing for >10% of the population were handled as categorical variables with up to four levels: “missing”, “below normal”, “normal”, and “above normal.” Otherwise, the tests were handled as continuous.…”
Section: Methodsmentioning
confidence: 99%
“…43 In 2020, in Denmark, the median length of stay at the hospital was four hours (IQR, 1;23) among patients with any unplanned (emergency) hospital contact including both injuries and diseases. 44 This finding is supported by other authors, 45 meaning than less than 25% of patients with an unplanned hospital contact will need a hospital stay lasting more than 24 hours. This indicates that most patients will have critical diseases ruled out or will be diagnosed with less urgent diseases not requiring hospital admission, advanced care or critical care.…”
Section: Emergency Carementioning
confidence: 64%
“…61,62 A corner stone in the recommendations was reducing the number of emergency hospitals receiving emergency patients around the clock from more than 44 to 21. 45,59,60 Also, in the same period, the increasing evidence regarding the association between higher patient volumes and better outcome of emergency care in, e.g., trauma, 63, 64 myocardial infarction 65,66 and stroke [67][68][69] , created a need to reorganise and centralise the treatment of selected time-dependent diseases in even fewer specialised centres. This resulted in the selection of four Danish trauma centres, four centres offering acute coronary interventions and six (later ten) stroke centres.…”
Section: Emergency Care As a Political Prioritymentioning
confidence: 99%